Effectiveness Various Physical Exercise to Decrease Glycemic Control in Patient with Diabetes Mellitus : A systematic review - Tifanny Gita Sesaria; Kusnanto Kusnanto; Abu Bakar (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Introduction : Physical exercise have been considered as on of ‘standart intervention’ in management of type 2 diabetes. Types of exercise that related with patients such as aerobic exercise, also resistance training. Nevertheless, there is still a low progress and prevalence of exercise in diabetes people Objectives : The aim of study for present effect of various physical exercise aerobic, resistance exercise also combined aerobic and resistance exercise to decrease Hba1c and blood glucose Method: Search the scientific article about diabetes and physical exercise in the database Scopus, PubMed, ProQuest, Spinger Link and Science Direct for original and full researchResult : The study review combined aerobicand resistance exercise improved the glycemic control of T2DM and it was widely used and significant for glycemic controlConclusion: This systematic review could be used as evidence when increase combine aerobic and resistance exercise as choice physical exercise interventions for the purpose of glycemic control